Bibliometric Review of Bilingual Education Between 1983 and 2023 (40 Years) - Chuan-Chung Hsieh; Anh Hoang Khau; Jr-Yan Shen (SAGE Open)
This bibliometric review explores global research trends in bilingual education over the past four decades (1983–2023), using co-citation analysis, bibliographic coupling, and keyword co-occurrence. An analysis of 1,716 articles indexed in the Web of Science identifies key topics, influential scholars, and emerging research frontiers. In the review, significant themes include promoting bilingualism, implementing bilingual education policies, translanguaging, Content-Language Integrated Learning (CLIL), and English-medium instruction (EMI). The results also revealed that culturally responsive pedagogies and peer support were successful approaches in the program. Bilingual instruction is additionally becoming more well-known in Asian nations, centring on CLIL and EMI approaches, which have benefits and challenges. Besides, the review clarifies that inclusive bilingual education is not just about bringing students’ linguistic and cultural background into the curriculum but also about a need to focus on approaches, such as using Strategic and Interactive Writing Guide methodology to help deaf and hard-of-hearing students perform better in Sign Bilingual Education. It may be helpful for scholars of interest to refer to bilingual education models/approaches based on these results.